Tropical Bont Tick Amblyomma variegatum Fabricius (Arachnida: Acari: Ixodidae) - Karen C. Prine; Amanda C. Hodges (EDIS, 2012)
The tropical bont tick is considered one of the most detrimental of the tick species present in Africa and now the Caribbean. It can result in severe economic losses due to hide damage, milk production reduction, and death of livestock. This 7-page fact sheet was written by Karen C. Prine and Amanda C. Hodges, and published by the UF Department of Entomology and Nematology, June 2012.